Human+Human or Human+AI: A Comparative Analysis of a Narrative Visualization Design Guide - Borges, Mariana Gomes; Correa, Claiton Marques; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Narrative visualizations integrate storytelling techniques with data visualization to enhance user engagement and understanding. These visualizations facilitate a more intuitive grasp of complex information. In this context, we developed a guide to support designers in creating such visualizations. This guide outlines systematic steps to identify suitable narrative genres and data visualization techniques recommended for planning a narrative data visualization. The guide’s clarity and applicability were assessed through two studies. The first study, with data visualization professionals, allowed the guide’s utility to be evaluated in a real-world setting, with participants who bring specific industry experiences and knowledge. The second one, utilizing emerging AI technology, specifically ChatGPT 4.0, besides testing the guide’s comprehensibility and usability, enabled the analysis of using innovative applications for simulating user interactions. Considering the studies’ results, despite some adjustments, the guide proved especially beneficial for professionals without prior knowledge of narrative elements, as it clarified numerous queries and facilitated the visualization process. Interaction via ChatGPT 4.0 provided insights into the guide’s usability and effectiveness across different user types, suggesting further improvements. Based on the findings, the guide is proposed to be revised to incorporate the suggestions and then be re-evaluated in further studies. Additionally, the study brings a reflection on the interactions and outcomes with human professionals and with an AI tool, highlighting differences, similarities, and limitations, paving the way for the development of AI-driven recommendation tools that can dynamically suggest narrative structures and visualization techniques tailored to specific datasets and user needs.